UPAYA PEMERINTAH DAN ORANG TUA DALAM PENCEGAHAN MEROKOK PADA ANAK USIA â‰¥15 TAHUN DI JAWA TENGAH - Athallah, Fakhrizal Rafly; Wahyuningsih, Ili; Atiqoh, Nabila Sholihah; Karikasari, Saraswati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The problem of increasing the percentage of cigarette users aged ? 15 years in 2016 to 2018 in a row in Central Java Province requires a decrease in the percentage in the following year. This is related to the need for maximum health in child development. The purpose of this study is to determine the cause of the increase in the percentage of cigarette use at the age of ? 15 years in each year and to determine the role of government and parents in the prevention of smoking at the age of  15 years. This research is a type of quantitative research in which research interacts directly with respondents. The data validity technique uses data triangulation that utilizes sources, methods, and theories. This study uses qualitative data analysis techniques. The results of this study, of 5 respondents, 4 respondents stated if their parents did not know if they smoke, and 1 respondent stated that his parents knew if he smoked. The efforts of the government and parents in the prevention of smoking at the age of  15 years need an increase because of the increasing percentage position where the right of children to get healthy can be fulfilled